BODIPY-17α-ethynylestradiol conjugates: Synthesis, fluorescence properties and receptor binding affinities. Issue 3 (1st February 2017) - Osati, Samira; Ali, Hasrat; Marques, Fernanda; Paquette, Michel; Beaudoin, Simon; Guerin, Brigitte; Leyton, Jeffrey V.; van Lier, Johan E.
Graphical abstract: Abstract: In vivo imaging of estrogen receptor (ER) densities in human breast cancer is a potential tool to stage disease, guide treatment protocols and follow-up on treatment outcome. Both positron emission tomography (PET) and fluorescence imaging have received ample attention to detect ligand-ER interaction. In this study we prepared BODIPY-estradiol conjugates using 4, 4-difluoro-4-bora-3a, 4a-diaza-s-indacene (BODIPY) as fluorescent probe and estradiol derivatives as ligand and established their relative binding affinity (RBA) for the ERα. The synthesis of the conjugates involves attachment of a BODIPY moiety to the C17α-position of estradiol using Sonogashira or click reactions of iodo-BODIPY or aza-BODIPY with various 17α-ethynylestradiol (EE2) derivatives. The highest RBA for the ERα was observed with the EE2-BODIPY conjugate (7 ) featuring a linear eight carbon spacer chain. Cell uptake studies and in vivo imaging experiments in an ER-positive mouse tumor model are in progress.